Structure characteristics of Aspergillus egyptiacus mitochondrial genome, an important fungus during the fermentation of dark tea. Issue 2 (3rd July 2018) - Xu, Zhenggang; Wu, Liang; Liu, Shiquan; Chen, Yi; Zhao, Yunlin; Yang, Guiyan
Abstract: Aspergillus egyptiacus is an important fungus during the fermentation process of dark tea. However, there is little study on genetic information about A. egyptiacus. In this study, A. egyptiacus was is isolated from dark tea and first sequenced. The annotation and analysis also have been done for the mitochondrial genome. The length of A. egyptiacus mitochondrial genome is 66, 564 bp and include 41 genes. Similar to most fungus, 15 protein-coding genes (PCGs), 24 transfer RNA (tRNA) genes, 2 ribosomal RNA (rRNA) genes, and one non-coding control region (D-loop) were identified in the strand of mitochondrial genome. The GC content is 26.55% and the reconstructed phylogenetic supported the placement of A. egyptiacus in Eurotiomycetes clade. The mitochondrial genome information also may supply references for utilization of A. egyptiacus.